Mucosal associated invariant T cells are differentially impaired in tolerant and immunosuppressed liver transplant recipients. Issue 1 (28th June 2020) - Sattler, Arne; Thiel, Lion G.; Ruhm, Annkathrin H.; Bergmann, Yasmin; Dornieden, Theresa; Choi, Mira; Halleck, Fabian; Friedersdorff, Frank; Eurich, Dennis; Kotsch, Katja
Abstract : Mucosal associated invariant T (MAIT‐) cells represent a semi‐invariant T cell population responsive to microbial vitamin B metabolite and innate cytokine stimulation, executing border tissue protection and particularly contributing to human liver immunity. The impact of immunosuppressants on MAIT cell biology alone and in context with solid organ transplantation has not been thoroughly examined. Here, we demonstrate that in vitro cytokine activation of peripheral MAIT cells from healthy individuals was impaired by glucocorticoids, whereas antigen‐specific stimulation was additionally sensitive to calcineurin inhibitors. In liver transplant (LTx) recipients, significant depletion of peripheral MAIT cells was observed that was largely independent of the type and dosage of immunosuppression, equally applied to tolerant patients, and was reproducible in kidney transplant recipients. However, MAIT cells from tolerant LTx patients exhibited a markedly diminished ex vivo activation signature, associated with individual regain of functional competence toward antigenic and cytokine stimulation. Still, MAIT cells from tolerant and treated liver recipients exhibited high levels of PD1, accompanied by functional impairment particularly toward bacterial stimulation that also affected polyfunctionality. Our data suggest interlinked effects of primary liver pathology and immunosuppressive treatment on overall MAIT cell fitness after transplantation and propose their monitoring in context with tolerance induction protocols. Abstract : Human mucosal associated invariant T cells are significantly depleted, hyperactivated, and functionally impaired in liver transplant recipients, but partially recover after immunosuppression weaning in tolerant patients.